West Fertilizer Regulatory Legacy—EPA RMP Amendments. Issue 4 (3rd November 2020) - Cutchen, Steven
Abstract: On April 17, 2013, a fire and explosion occurred at the West Fertilizer Company in West, Texas. Twelve emergency responders and three members of the public died. More than 260 people were treated by local hospitals. The U.S. Chemical Safety and Hazard Investigation Board (CSB) investigated the incident. The CSB determined that about 40 percent of the 30 tons of fertilizer‐grade ammonium nitrate (FGAN) detonated to cause the explosion. The CSB found that there were no effective federal regulations of FGAN in effect at the time of the explosion. They subsequently describe the initial federal response to the explosion as of the date of the CSB report; an Executive Order for, among many other things, modernizing federal policies and regulations surrounding chemical facilities, including those storing FGAN such as West Fertilizer. Presented here is a followup report of this modernization, focusing on the changes that impact process safety. This effort initially took the form of amendments to the Environmental Protection Agency (EPA) regulation 40 C.F.R. § 68 Chemical Accident Prevention Provisions. Following the implementation of the amendments, the EPA subsequently took action to rescind the bulk of the changes.